CDK4/6 inhibitor resistance: A bibliometric analysis - Pang, Jiayuecheng; Li, Hengyu; Sheng, Yuan (Frontiers in Oncology, 2022)
Background Cyclin-dependent kinases (CDKs) 4/6 inhibitors are a type of cell cycle regulation that prevents cell proliferation by blocking retinoblastoma protein (Rb) phosphorylation in the G1 to S phase transition. CDK 4/6 inhibitors are currently used mainly in patients with hormone receptor-positive/ human epidermal growth factor receptor 2 (HER2) negative breast cancer in combination with endocrine therapy. However, primary or acquired resistance to drugs severely affect drug efficacy. Our study aims at summarizing and visualizing the current research direction and development trend of CDK4/6 inhibitor resistance to provide clinicians and research power with a summary of the past and ideas for the future. Methods The Web of Science Core Collection and PubMed was searched for all included articles on CDK4/6 inhibitor resistance for bibliometric statistics and graph plotting. The metrological software and graphing tools used were R language version 4.12, Bibliometrix 3.2.1, Vosviewer 1.6.18, GraphPad Prism 9, and Microsoft Excel 2019. Results A total of 1278 English-language articles related to CDK4/6 inhibitor resistance were included in the Web of Science core dataset from 1996-2022, with an annual growth rate of14.56%. In PubMed, a total of 1123 articles were counted in the statistics, with an annual growth rate of 17.41% Cancer Research is the most included journal (102/1278, 7.98%) with an impact factor of 13.312 and is the Q1 of the Oncology category of the Journal Citation Reports. Professor Malorni Luca from Italy is probably the most contributing author in the current field (Publications 21/1278, 1.64%), while Prof. Turner Nicholas C from the USA is perhaps the most authoritative new author in the field of CDK4/6 inhibitor resistance (Total Citations2584, M-index 1.429). The main research efforts in this field are currently focused on Palbociclib and Abemaciclib. Studies on drug resistance mechanisms or post-drug resistance therapies focus on MEK inhibitors and related pathways, PI3K-AKT-MTOR pathways or inhibitors, EGFR-related pathways, EGFR inhibitors, TKI inhibitors, MAPK pathways and inhibitors, and so on. Conclusion This study provides researchers with a reliable basis and guidance for finding authoritative references, understanding research trends, and mining research neglect directions.